Optimization of yield for circulating tumour cell separation using integrated dielectrophoretic-magnetophoretic technique / Low Wan Shi - Low, Wan Shi (2017)
Cell based cancer analysis is an important analytic methods to monitor cancer progress on stages by detecting the density of circulating tumour cells (CTCs) in the blood. Among the existing microfluidic techniques, dielectrophoresis (DEP), which is a label-free detection method, is favoured by researchers. However, because of the high conductivity of blood as well as the rare presence of CTCs, high separation efficiency is difficult to be achieved in most DEP microdevices. Therefore, this study was conducted with the aim of improving the isolation performance of a DEP device, as such by integrating with magnetophoretic (MAP) platform. Several important aspects to be taken into MAP design consideration, such as permanent magnet orientation, magnetic track configuration, fluid flow parameter and separation efficiency, are discussed. The design was examined and validated by numerical simulation using COMSOL Multiphysics v4.4 software, mainly presented in three form: surface plot, line plot and arrow plot. The simulation results showed that the use of single permanent magnet coupled with an inbuilt magnetic track of 250m significantly strengthens the magnetic field distribution within the proposed MAP stage. Besides, in order to improve dynamic pressure without compromising the uniformity of fluid flow, a wide channel inlet and a tree-like network were employed. When the cell trajectory within a finalized MAP stage is computed with a particle tracing module, a high separation efficiency of RBC is obtained for blood sample corresponded up to a dilution ratio of 1:10. Moreover, a substantial enhancement of CTCs recovery rate was also observed in the simulation when the purposed platform is integrated with a planar DEP microdevice.